Nesfatin-1 and other hormone alterations in polycystic ovary syndrome - Deniz, Rulin; Gurates, Bilgin; Aydin, Suleyman; Celik, Husnu; Sahin, Ibrahim; Baykus, Yakup; Gungor, Sami (Springer, 2012)
Polycystic ovary syndrome (PCOS) is commonly characterised by obesity, insulin resistance (IR), hyperandrogenemia and hirsutism. Nesfatin-1 a recently discovered hormone, acts upon energy balance, glucose metabolism, obesity and probably gonadal functions. This study was to evaluate the circulating levels of nesfatin-1 in patients with PCOS (n = 30) and in age and body mass index (BMI)-matched controls (n = 30). PCOS patients had significantly lower levels of nesfatin-1 (0.88 +/- A 0.36 ng/mL) than healthy controls (2.22 +/- A 1.14 ng/mL). PCOS patients also had higher gonadotropin and androgen plasma concentrations, Ferriman-Gallwey scores, blood glucose levels and a homeostasis model of assessment-IR index (HOMA-IR) index than in healthy women. Correlation tests in PCOS subjects detected a negative correlation between nesfatin-1 levels and BMI, fasting blood glucose, insulin levels and a HOMA-IR index. Lower nesfatin-1 concentration may plays a very important role in the development of PCOS.
Keywords: PCOS; Nesfatin-1; Ferriman-Gallwey scores